PERANAN DAN FUNGSI KEPALA MADRASAH SEBAGAI PEMIMPIN PENDIDIKAN DI MADRASAH IBTIDAIYAH SWASTA IKHWANUL MUSLIMIN TEMBUNG II - Najah, Nadiah; Syukri, Makmur (Program Studi Manajemen Pendidikan Islam, 2024)
This research aims to explore the role and function of the headmaster as an educational leader at the Ikhwanul Muslimin Private Elementary School, Tembung II. This study employs a descriptive qualitative approach and uses library research as the research model. Data collection techniques include documentation study and interviews with key informants. The study found that the headmaster plays a crucial role in managing the school, fostering a conducive learning environment, and promoting Islamic values. The analysis of data reveals that effective leadership, characterized by clear vision, strong communication, and supportive behavior, enhances the overall performance of the school. The study concludes that the headmaster's leadership influences academic achievement, student discipline, and school reputation. It recommends that future research focus on the impact of leadership styles on student outcomes and the development of leadership training programs for educational leaders